REKONSTRUKSI KETENTUAN HAK KORBAN KEKERASAN DALAM RUMAH TANGGA (KDRT) SEBAGAI UPAYA PEMENUHAN HAK EKONOMI KORBAN KDRT - Nur Farida; Rusdianto Sesung; Febrian Rizki Pratama (Bajang Institute, 2026)
Domestic violence not only causes physical and psychological injuries to victims, but also results in economic losses. Article 10 of Law No. 23 of 2004 on the Elimination of Domestic Violence stipulates that the rights of victims focus solely on the recovery of physical and psychological injuries, while economic rights are not the focus of protection. The purpose of this study is to examine the considerations for regulating the economic rights of victims of domestic violence and to examine the forms of economic rights that victims can obtain. The research method is a normative juridical method using a statute approach, a conceptual approach, and a case approach. From this research, it can be concluded that the regulation of economic rights in the Law on the Elimination of Domestic Violence is a legal instrument to ensure that victims are not only physically protected but also have the financial resilience to continue living independently, whereby the regulation requires the fulfilment of rights that are adaptive to the status of the victim's relationship